A feminist theory of refusal - Honig, Bonnie (Harvard University Press, 2021)
"Bonnie Honig invigorates debate over the politics of refusal by insisting that withdrawal from unjust political systems be matched with collective action to change them. Historical and fictional characters from Muhammad Ali to the Bacchants of ancient Greek tragedy teach us how to turn rejection into transformative efforts toward self-governance"--